2021
DOI: 10.7498/aps.70.20210013
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of hydrogen bond vibrations of ice

Abstract: Despite its simple molecular structure, water is still a mystery to scientists. For the atomic and molecular vibrational modes of ice, as is well known, there are two kinds of vibrations: intra-molecular O—H stretching vibration and H—O—H bending vibration within the molecules and three kinds of molecular spatial rotations. However, thirty years ago, a high flux inelastic neutron scattering experiment showed that there are two distinct characteristic peaks in the far-infrared molecular translational vibration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 157 publications
2
25
0
Order By: Relevance
“…Then, we confirmed that the two distinct HB peaks in ice Ih originated from these two kinds of HB modes [19]. By now, we have investigated almost all the ice phases, thereby determining that this is a general rule for ice because of its local tetrahedral structure [18]. Based on these new findings, we have obtained a deeper understanding of the HB interactions in water ice and their broad role in nature.…”
Section: Discussionsupporting
confidence: 60%
See 4 more Smart Citations
“…Then, we confirmed that the two distinct HB peaks in ice Ih originated from these two kinds of HB modes [19]. By now, we have investigated almost all the ice phases, thereby determining that this is a general rule for ice because of its local tetrahedral structure [18]. Based on these new findings, we have obtained a deeper understanding of the HB interactions in water ice and their broad role in nature.…”
Section: Discussionsupporting
confidence: 60%
“…The two intrinsic HB vibrational modes originate from the local tetrahedral geometry of the ice lattice. This finding has proved to be a general rule for the ice family [18]. For ice phases under atmospheric pressure, such as ices Ih, XI, and Ic, the two characteristic HB peaks can be easily explained by the existence of two kinds of HB vibrational modes.…”
Section: Resultsmentioning
confidence: 63%
See 3 more Smart Citations